Halotolerance, ligninase production and herbicide degradation ability of basidiomycetes strains - Arakaki, R.l. [UNESP]; Monteiro, D.a. [UNESP]; Boscolo, M. [UNESP]; Dasilva, R. [UNESP]; Gomes, E. [UNESP] (Sociedade Brasileira de Microbiologia, 2013)
Fungi have been recently recognized as organisms able to grow in presence of high salt concentration with halophilic and halotolerance properties and their ligninolytic enzyme complex have an unspecific action enabling their use to degradation of a number of xenobiotic compounds. In this work, both the effect of salt and polyols on growth of the basidiomycetes strains, on their ability to produce ligninolytic enzyme and diuron degradation were evaluated. Results showed that the presence of NaCl in the culture medium affected fungal specimens in different ways. Seven out of ten tested strains had growth inhibited by salt while Dacryopinax elegans SXS323, Polyporus sp MCA128 and Datronia stereoides MCA167 fungi exhibited higher biomass production in medium containing 0.5 and 0.6 mol.L-1 of NaCl, suggesting to be halotolerant. Polyols such as glycerol and mannitol added into the culture media improved the biomass and ligninases production by D. elegans but the fungus did not reveal consumption of these polyols from media. This fungus degraded diuron in medium control, in presence of NaCl as well as polyols, produced MnP, LiP and laccase.
Keywords: Basidiomycetes; halotolerance; Ligninases; diuron degradation